Mandibular reconstruction with deep circumflex iliac artery osteomyocutaneous free flap in a severe case of osteoradionecrosis of the mandible: a case report / Namkabir Singh ... [et al.] - Singh, Namkabir; Kong, Chee Kwan; Ismail, Siti Mazlipah; Abdul Khalil, Alizan (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
Introduction Osteoradionecrosis (ORN) can be accompanied by several signs such as tissue loss, exposed necrotic bone, presence of fistula, pain, infection, trismus, and even pathological fracture of bones. Early-stage ORN is usually managed conservatively with medication while severe progression of the disease requires aggressive treatment such as free flap reconstruction surgery. Case report This case involves a 52-year-old lady who was previously diagnosed with well-differentiated squamous cell carcinoma of the left side of the tongue (T3 N2b M0) and had undergone surgery, followed by 6 cycles of chemotherapy and 30 cycles of radiotherapy. She presented to our centre complaining of pain and pus discharge over her lower jaw for the past 3 months. Upon examination, the skin around her neck and chin was erythematous, firm and tense, limiting not just her mouth opening but also the flexibility of her neck movement. She also had two oralcutaneous fistulas, at the submental and submandibular region, with thick pus discharge. Intraorally, there was a broken and exposed titanium plate. She was subjected to segmental resection of the anterior mandible together with fistulectomy, reconstruction with deep circumflex iliac artery osteomyocutaneous flap and tracheostomy. Conclusion Despite not being a life-threatening disease, ORN has a significant impact on the well-being of patients, leaving them with possible disfiguration, pain and chronic wounds. This case report summarizes the journey of our patient from initial presentation, surgery, and post operative follow-up, highlighting the rare need for aggressive treatment in managing advanced ORN.